New social movements, ethnic and regional political discourse Angaraes, Huancavelica - Plasencia Soto, Rommel (2014)
An important idea is of etnopolítica, that is to say when a group or movement believes that for his cultural attribute it is a subject of discrimination, or when the ethnic identity uses (a term more restricted than that of culture) to obtain advantages and resources of the company, and that for it takes part of the political competition. e Peruvian case is not an exception.